До питання синхронізації приводних двигунів вібромашин для обробки довгомірних деталей - Калмыков, Михаил Александрович; Романченко, Алексей Владимирович; Локотош, Борис Николаевич; Яковенко, Валерий Владимирович (Eastern-European Journal of Enterprise Technologies, 2010)
The analysis of work of the synchronization system of oscillation machine-tool engines is conducted on the chart of electric billow. The method of calculation of stability of work of the synchronization system of oscillation machine-tool drive is developed